Strategi Pemasaran Digital Wisata Watu Gendong Desa Beji Kecamatan Ngawen Kabupaten Gunungkidul untuk Menarik Minat Kunjungan Wisatawan - Aji Tegar Herlambang; Erlangga Brahmanto (Journal of Economic and Business Advancement, 2026)
This study examines the digital marketing strategies implemented at Watu Gendong Tourism Village, Beji Village, Ngawen District, Gunungkidul Regency, and their role in stimulating tourists’ intention to visit. Employing a field-based qualitative research design, the study integrates in-depth interviews, participant observation, and documentation analysis to capture strategic practices, managerial dynamics, and audience engagement patterns within the destination’s digital promotion ecosystem. The findings reveal that digital marketing effectiveness is strongly shaped by the strategic alignment between visual storytelling, platform selection, and interactive communication with potential visitors. Social media utilization, particularly through visually driven and narrative-based content, contributes to the formation of destination image, perceived authenticity, and emotional attachment among prospective tourists. The active involvement of local stakeholders in content production and online interaction enhances credibility and strengthens digital engagement